Cleavage-Mediated Regulation of Myd88 Signaling by Inflammasome-Activated Caspase-1 - Avbelj, Monika; Hafner-Bratkovič, Iva; Lainšček, Duško; Manček-Keber, Mateja; Peternelj, Tina Tinkara; Panter, Gabriela; Treon, Steven P.; Gole, Boris; Potočnik, Uroš; Jerala, Roman (Frontiers in Immunology, 2022)
Coordination among multiple signaling pathways ensures an appropriate immune response, where a signaling pathway may impair or augment another signaling pathway. Here, we report a negative feedback regulation of signaling through the key innate immune mediator MyD88 by inflammasome-activated caspase-1. NLRP3 inflammasome activation impaired agonist- or infection-induced TLR signaling and cytokine production through the proteolytic cleavage of MyD88 by caspase-1. Site-specific mutagenesis was used to identify caspase-1 cleavage site within MyD88 intermediary segment. Different cleavage site location within MyD88 defined the functional consequences of MyD88 cleavage between mouse and human cells. LPS/monosodium urate–induced mouse inflammation model corroborated the physiological role of this mechanism of regulation, that could be reversed by chemical inhibition of NLRP3. While Toll/interleukin-1 receptor (TIR) domain released by MyD88 cleavage additionally contributed to the inhibition of signaling, Waldenström’s macroglobulinemia associated MyD88L265P mutation is able to evade the caspase-1-mediated inhibition of MyD88 signaling through the ability of its TIRL265P domain to recruit full length MyD88 and facilitate signaling. The characterization of this mechanism reveals an additional layer of innate immunity regulation.